DISEASE CONTROL USING BIOPESTICIDE ON RICE PLANTS (Oryza sativa L.) - Jonatan Monareh; Tommy B. Ogie (Sam Ratulangi University, 2020)
Indonesia is an area that has excellent potential in the agricultural sector, so that at the international level Indonesia is one of the world's largest producers and consumers of rice under China. Rice is a rice-producing food crop commodity that plays an important role in Indonesia's economic life. Rice plant disease is leaf blight caused by bacteria (Xanthomonas campestris pv. Pryzae), tugro disease (tugro virus), pyricularia fungal leaf spot (Pyricularia grisea), stem rot (Helminthosporium sigmoideun), leaf blight (Rhizoctonia solani Kuhn), empty stunts (reget stunts) and grassy stunts (Nuryanto, 2018). loss of agricultural production due to pest attack is Â± 30% of the potential yield, and loss of yield due to disease is around 20-25% (Untung, 2010).Â Keywords: Rice; leaf blight; biopesticides.AbstrakIndonesia merupakan daerah yang memiliki potensi yang sangat baik pada sektor pertanian, sehingga Indonesia di tingkat internasional merupakan salah satu produsen sekaligus konsumen beras terbesar dunia di bawah Cina. Padi merupakan komoditas tanaman pangan penghasil beras yang memegang peranan penting dalam kehidupan ekonomi Indonesia. Penyakit tanaman padi adalah hawar daun yang disebabkan oleh bakteri (Xanthomonas campestris pv. Pryzae), penyakit tugro (Virus tugro), bercak daun jamur pyricularia (Pyricularia grisea), busuk batang (Helminthosporium sigmoideun), hawar pelepah daun (Rhizoctonia solani Kuhn), kerdil hampa (reget stunt) dan kerdil rumput (grassy stunt) (Nuryanto, 2018). kehilangan hasil produksi pertanian karena serangan OPT Â±30% dari potensi hasil, dan kehilangan hasil karena penyakit sekitar 20-25% (Untung, 2010).Kata kunci: Padi; penyakit hawar daun; biopestisida.